1984
DOI: 10.1111/j.1600-0765.1984.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic change in cultured gingival fibroblasts exposed to bacterial extracts

Abstract: Hyaluronic acid synthesis was studied in human gingival fibroblast cultures exposed to bacterial extracts from dental plaque, Bacillus cereus, and Escherichia coli (lipopolysaccharide, LPS). Dental plaque extract was the best stimulant of hyaluronic acid synthesis. B. cereus extract was almost as effective, but the effect of LPS was insubstantial. This indicates that gram‐positive microorganisms of dental plaque, as well as gram‐negative bacteria, may be involved in the stimulation of hyaluronic acid synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several in viiro studies have indeed demonstrated that bacterial plaque extracts and sonicates of cultured bacteria decrease the prohferation and collagen synthesis of connective tissue cells in culture (20,21,22,23). Exposure of fibroblasts to bacterial products also increases the production of hyaluronic acid, collagenase, and interleukin 1 (20,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Several in viiro studies have indeed demonstrated that bacterial plaque extracts and sonicates of cultured bacteria decrease the prohferation and collagen synthesis of connective tissue cells in culture (20,21,22,23). Exposure of fibroblasts to bacterial products also increases the production of hyaluronic acid, collagenase, and interleukin 1 (20,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…At higher concentrations lipopolysaccharide from different bacterial species inhibits cell proliferation (8,134). Lipopolysaccharide as well as bacterial plaque extracts increase hyaluronan production in cultured gingival fibroblasts (7,130). Hyaluronan is a high-molecularweight polyanionic glycosaminoglycan that plays an important role in wound healing through specific interaction with other matrix molecules and cells (23).…”
Section: Role Of Bacteria In Oral Wound Healingmentioning
confidence: 99%
“…Since several gram-negative species have been implicated in the pathogenesis of the more severe forms of the periodontal diseases, several studies have focused on the biological activity of LPS (1)(2)(3)11). Among the many and varied effects of LPS is an ability to alter fibroblast metabolic activity (9,19,20,37). Gingival fibroblasts are primarily responsible for maintaining the structural components of the periodontium in a state which will permit adequate physiological function.…”
Section: Resultsmentioning
confidence: 99%
“…Of these components, lipopolysaccharide (LPS) has received considerable attention (1)(2)(3)11). To date, it has been shown that LPS can modulate cell growth (21,36,40), synthetic activity (9,19,20), and bone metabolism (17, 24) as well as stimulate macrophages to secrete a variety of lymphokines (16). Thus, this cell surface component of gram-negative bacteria has the capacity to significantly alter the physical properties of tissues either directly by influencing the connective tissue cells or indirectly by inducing an inflammatory response.…”
mentioning
confidence: 99%